Proteome Analysis of Camellia nitidissima Chi Revealed Its Role in Colon Cancer Through the Apoptosis and Ferroptosis Pathway - Chen, Yiwei; Zhang, Fan; Du, Zhengcai; Xie, Jinling; Xia, Lei; Hou, Xiaotao; Hao, Erwei; Deng, Jiagang (Frontiers in Oncology, 2021)
Colon cancer is the third most common cancer in the world with a high mortality rate. At present, surgery combined with radiotherapy and chemotherapy is the primary treatment, but patient prognosis remains poor. Traditional Chinese medicine (TCM) has become a complementary and alternative source of anti-cancer drugs. Camellia nitidissima Chi (CNC) is a TCM used to treat a variety of cancers. However, the role of CNC in cancer remains elusive, and its effect and mechanism on colon cancer have not been reported. Here, we show that CNC exerts an excellent inhibitory effect on colon cancer proliferation in vitro and in vivo. We performed label free-based quantitative proteomic analysis to evaluate the HCT116 cells treated with CNC. Our data revealed a total of 363 differentially expressed proteins, of which 157 were up-regulated and 206 down-regulated. Gene Ontology enrichment analysis showed that these proteins were involved in tumor occurrence and development through multiple biological processes such as cell proliferation, cell cycle, and cell death. Interestingly, we also found significant changes in ferroptosis pathways. The role of essential proteins glutathione peroxidase 4 (GPX4) and heme oxygenase-1 (HMOX1) were verified. CNC decreased the expression of GPX4 and increased the expression of HMOX1 at the mRNA and protein levels in vivo and in vitro. Collectively, these findings reveal that CNC regulates colon cancer progression via the ferroptosis pathway and could be an attractive treatment for colon cancer.